Application of the Stake Evaluation Model to evaluate Kurikulum Merdeka in creating student well-being - Risti Dwi Lestari (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
The demographic bonus has become unavoidable for Indonesia in 2030–2045. Will this condition be advantageous or disadvantageous depending on how HR is currently managed? The scope of HR management in this study is in the field of education, and the main actor is the government. Bearing in mind that in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia Article 31 (1) and its Amendment Chapter XIII concerning education and culture, obliges the government to be responsible for educating the life of the nation and creating general welfare? This study aims to determine the appropriate evaluation model to assess the implemented curriculum with regard to the welfare of students through the characteristics of a